Cervical cytology profile by Papanicolaou smear in a rural setting in mid-Kerala - Jayaprakash, Megha; Menon, Sreenija; Eralil, Georgy Joy; K. P., Alok; Jose, Rajany (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: With no systematic national screening programme, the rates of cervical epithelial cell abnormalities as reported by various studies range from 1.32% to 25% in India. Majority are epithelial squamous cell abnormalities that include atypical squamous cells of undetermined significance (ASCUS) and low-grade squamous intraepithelial lesion (LSIL). Worldwide incidence of adenocarcinoma and its precursors have increased over past few decades. Objectives were to study the clinical and cervical cytological profile among women attending camps in rural areas of Thrissur district of Kerala. Methods: A cross sectional study was conducted in 214 women in the 25-65 years age group who attended cancer screening camps in rural areas of Thrissur district. Papanicolaou (Pap) smear was done using standard technique and reported using latest Bethesda classification. Pap smear results were considered as abnormal when the report was ASCUS, atypical glandular cells of undetermined significance, LSIL, high grade squamous intraepithelial lesion or invasive lesion. Results: Of all the smears, 41.6% were negative for intraepithelial lesion or malignancy. Inflammatory smears (nonspecific and specific infection associated) were seen in 57%. Glandular cell abnormality was found in 1.4% and these women were in 31-50 years age group. Among patients with glandular cell abnormality most common symptom was discharge per vaginum. Conclusions: The results of this study may be a pointer to an increase in glandular cytological abnormalities in our population and needs further large-scale studies to confirm. Current screening methods of Pap smear alone may not be adequate to pick up these lesions.